Urban growth trends in city of Taif Analyzed with geographical information systems - Bin Dfran, Adnan Ibrahim Mussaed; Abbakar, Mustafa Mohamed Ali (Journal of Humanities & Social Sciences, 2022)
This study sought to determine trends in urban growth between (1380 Ah-1440 Ah) of Taif city as one of the main provinces of mecca. The city of Taif is also witnessing rapid urban and population growth, which led to the expansion of the city of Taif significantly in the north-east direction, so this study aimed to determine the direction of this expansion and its proportion through the use of modern technologies GIS and remote sensing in the process of processing, analysis and interpretation of space visuals obtained from King Abdul Aziz City of Science and Technology and digital and paper maps from the Ministry of Municipal and Rural Affairs and then to reach the desired results. By highlighting the results, the results showed a 39-kilometer urban extension to the northeast of the city center due to the easy nature of the land and the remoteness of the rugged mountainous areas. One of the most prominent recommendations of the study is to take care of roads and link new neighborhoods to the old in new ways, as the population is increasing and the roads are still the same as they have not kept pace with this expansion. Work to develop neighborhood’s and model schemes in the north-east and provide key services in order to create.